An Interdependence Theory of Wedge Strategies. (14th May 2020) - Huang, Yuxing
Abstract: A wedge strategy is a state's attempt to prevent, break up, or weaken a threatening or blocking alliance. An asymmetric alignment consists of a great power (the alignment leader) and a small/middle power (the weaker ally). So when does the wedge strategy of a great power (a divider) towards a competitive asymmetric alignment work? I propose, based upon the 'Crawford–Izumikawa debate', an 'interdependence theory' of wedge strategies. In the case of an asymmetric alignment that is symmetrically interdependent, the wedge strategy of a divider that accommodates the weaker ally is most likely to succeed. However, a wedge strategy towards an asymmetric alignment that is asymmetrically interdependent is highly likely to fail. I evaluate the theory based upon four wedge strategies adopted in Cold War Asia through analysing American, Russian, and Chinese archival sources. As asymmetrically interdependent, the US–Japan and US–Taiwan alliances offset the impact of Chinese wedge strategies. Between 1955 and 1965, therefore, neither Chinese accommodation nor Chinese pressure could detach weaker American allies from the United States in East Asia. However, China successfully exploited the symmetric interdependence of the US–Pakistan alliance. Between 1962 and 1965, China's accommodation of Pakistan prevented Pakistan from being used as an American base for containment purposes. Likewise, the Soviet Union took full advantage of the Sino–Vietnamese alignment's symmetric interdependence, whereby Soviet aid to North Vietnam caused rifts in Sino–Vietnamese relations that eventually wrecked the Sino–Vietnamese alignment. According to the theory, therefore, given the asymmetric interdependence of the hub-and-spokes system, any Chinese attempts to weaken US-sponsored alliances in East Asia would not be effective.